A "Geodetic Gap" in the Calabrian Arc: Evidence for a Locked Subduction Megathrust?. Issue 4 (20th February 2018) - Carafa, M. M. C.; Kastelic, V.; Bird, P.; Maesano, F. E.; Valensise, G.
Abstract: Subduction of old Ionian seafloor beneath the Calabrian Arc (southern Italy) is the geological process with the greatest mass flux in the central Mediterranean, yet its seismogenic behavior is largely obscured. No unambiguous evidence of subduction‐related earthquakes exists in historical times, and local GPS velocities indicate very low strain rates. Nevertheless, the region hosted some of the deadliest normal‐faulting earthquakes of the entire Mediterranean basin. We show that the low strain rates recorded in southern Calabria can be reconciled with the regional vigorous seismic moment release by assuming high interseismic coupling but low seismic coupling of the subduction interface. The alternative scenario of steadily creeping subduction cannot be ruled out but requires the historical seismicity record to be dismissed as unrepresentative. We refer to the peculiar spatial pattern of short‐term strain rates in southern Calabria as a "geodetic gap" resulting from destructive interference between upper‐plate extension and temporary compression due to locking along the subduction interface. Seismic hazard modelers must understand that within such gaps, the long‐term seismic hazard is greater than that suggested by the low geodetic strain rates. Plain Language Summary: Active subduction zones are the most dangerous seismogenic areas on our planet. Some may be especially elusive, however, and assessing their earthquake potential may be fraught with substantial uncertainties. Subduction of the Ionian seafloor beneath Calabria, an earthquake‐prone region of southern Italy, is one such case. Historically, Calabria has been struck by large earthquakes generated at crustal depth, that is, above the ongoing subduction, but no evidence is available for the activity of the underlying megathrusts. Is the subduction unlocked and creeping, thus posing no additional threat to the region or is it locked—at least partially—and capable of major yet very rare earthquakes? We used GPS velocities to address this issue and found that the recorded tectonic strain is well below the minimum needed to justify the known crustal seismicity. How so? Joint computer modeling of crustal and subduction‐related deformation showed us that Southern Calabria may be the locus of a "geodetic gap, " where subduction‐related strains are temporarily canceled out by crustal strains. This may be an indication that the subduction is indeed locked and hence capable of major tsunamigenic earthquakes. Geodetic gaps are themselves extremely elusive and may occur in other subduction zones worldwide. Key Points: Geodetic data do not preclude that the Calabrian subduction is locked and loading Geodetic strain rates can be reconciled with seismicity by assuming high interseismic coupling but low seismic coupling of the subduction interface We refer to the destructive interference between extensional and compressional strain rates as a "geodetic gap"